Structure and thermal stability of phosphorus-iodonium ylids - Greener, Andrew; Argent, Stephen P.; Clarke, Coby J.; O’Duill, Miriam L. (Beilstein Journal of Organic Chemistry, 2024)
Hypervalent iodine(III) reagents have become indispensable tools in organic synthesis, but gaps remain in the functionalities they can transfer. In this study, a fundamental understanding of the thermal stability of phosphorus-iodonium ylids is obtained through X-ray diffraction, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Insights into the structural factors affecting thermal stability and potential decomposition pathways will enable the future design and development of new reagents.
Keywords: hypervalent iodine; reagent development; structural analysis; thermal stability; thermogravimetric analysis